Nutritional limitations of mangosteen seedlings - Cardoso Moraes, Larissa Alexandra Cardoso; Garcia, Terezinha Batista; Moreira, Adônis (Pesquisa Agropecuaria Brasileira, 2006)
This work had the objective to evaluate, by foliar analysis, the nutritional limitations to the production of mangosteen seedlings. After 12 months in the nursery, under shade in the initial development, a progressive yellowing of the young leaves was observed, together with significant reduction of Fe and Mn concentrations in the leaf. Foliar sprays of Mn 0.8 mg L-1 as MnSO4 plus 2.5 g L-1 of urea was ineffective to recover green color of the leaf blades. However, this was achieved with application of Fe 0.8 mg L-1, as FeSO4, plus 2.5 g L-1 of urea, with increase of regreening, which highlights the low Fe absorption efficiency of mangosteen, despite the high concentration of this nutrient in the substrate of surface soil (223.7 mg dm-3). This indicates the need of application of Fe in the substrate or on the leaves, during the nursery stage of mangosteen.
Keywords: Garcinia mangostana; macronutrients; micronutrients; visual diagnosis; foliar diagnosis